Enhancing equitable access to rare disease diagnosis and treatment around the world: a review of evidence, policies, and challenges - Adachi, Takeya (2023)
This document provides a comprehensive summary of evidence on the current situation of rare diseases (RDs) globally and regionally, including conditions, practices, policies, and regulations, as well as the challenges and barriers faced by RD patients, their families, and caregivers. The document builds on a review of academic literature and policies and a process of validation and feedback by a group of seven experts from across the globe. Panelists were selected based on their academic merit, expertise, and knowledge regarding the RD environment. The document is divided into five main sections: (1) methodology and objective; (2) background and context; (3) overview of the current situation and key challenges related to RDs covering six dimensions: burden of disease, patient journey, social impact, disease management, RD-related policies, and research and development; (4) recommendations; and (5) conclusions. The recommendations are derived from the discussion undertaken by the experts on the findings of this review and provide a set of actionable solutions to the challenges and barriers to improving access to RD diagnosis and treatment around the world. The recommendations can support critical decision-making, guiding efforts by a broad range of RDs stakeholders, including governments, international organizations, manufacturers, researchers, and patient advocacy groups.